2010
DOI: 10.1128/aac.01638-09
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Candida albicans Biofilms with Antifungals: Transcriptional Response and Binding of Antifungals to Beta-Glucans

Abstract: Candida albicans can form biofilms that exhibit elevated intrinsic resistance to various antifungal agents, in particular azoles and polyenes. The molecular mechanisms involved in the antifungal resistance of biofilms remain poorly understood. We have used transcript profiling to explore the early transcriptional responses of mature C. albicans biofilms exposed to various antifungal agents. Mature C. albicans biofilms grown under continuous flow were exposed for as long as 2 h to concentrations of fluconazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(124 citation statements)
references
References 73 publications
4
118
0
2
Order By: Relevance
“…Although the FIC index assessment could be not fully appropriate in this situation, in which one of the agents is an enzyme with no effect on its own, some conclusions can be drawn. Data emerging from the C. albicans biofilm field demonstrate that AMB, facilitated by the amphiphilic nature, physically binds to ␤-1,3-glucans, a structural component of the fungal cell wall as well as the C. albicans biofilm ECM (41), and such a drug-sequestering ECM might hamper the polyene from reaching biofilm cells. So, it is plausible that the lowering of antifungal MICs for A. fumigatus biofilms in the presence of AlgL detected here could be ascribed to a nonspecific degradation of the ECM by the enzyme, thus enabling both AMB and LAMB to exert their antifungal action.…”
Section: Resultsmentioning
confidence: 99%
“…Although the FIC index assessment could be not fully appropriate in this situation, in which one of the agents is an enzyme with no effect on its own, some conclusions can be drawn. Data emerging from the C. albicans biofilm field demonstrate that AMB, facilitated by the amphiphilic nature, physically binds to ␤-1,3-glucans, a structural component of the fungal cell wall as well as the C. albicans biofilm ECM (41), and such a drug-sequestering ECM might hamper the polyene from reaching biofilm cells. So, it is plausible that the lowering of antifungal MICs for A. fumigatus biofilms in the presence of AlgL detected here could be ascribed to a nonspecific degradation of the ECM by the enzyme, thus enabling both AMB and LAMB to exert their antifungal action.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it protects against phagocytic cells and works as a scaffold for preserving biofilm integrity by limiting the diffusion of noxious substances into the biofilm [32]. Although biofilm resistance is multifactorial [33], the protection exerted by the ECM is a key factor in the high levels of antifungal drug resistance displayed by C. albicans biofilms [13,14,34]. It has been demonstrated that transcriptional regulatory genes in C. albicans, including TEC1 and EFG1, regulate biofilm formation [23,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal resistance in Candida biofilms is multifactorial and is associated with the physiological state of the cells, the activation of drug efflux pumps, and the protective effect of the ECM performed by β-glucans [alkali-soluble polysaccharides (ASPs)], which bind to fluconazole [13] and amphotericin B, preventing the penetration of drugs into the biofilm [14]. In addition to the protective effects of the ECM due to β-glucan, it has been shown that the extracellular DNA (eDNA) is another key component contributing to the structural integrity of C. albicans biofilms [15].…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal resistance of Candida biofilms is multifactorial and involves the stimulation of drug efflux pumps, the physiological state of cells, and the protection exerted by the ECM via β-glucans that bind to FLZ and amphotericin B [22], which limits diffusion of these antifungals through biofilms [23]. C. albicans biofilms that grow under constant flow produce higher quantities of ECM than statically cultured biofilms.…”
Section: Introductionmentioning
confidence: 99%